Perception of Political Leadership in Local Governments in Latvia - Stučka, Malvīne (Socialiniai tyrimai, 2018)
Theme of the paper is political leadership in local governments in Latvia. The work uses secondary data analysis and case studies. The aim of the study is to find out what kind of role does the chairperson of the municipality have as a political leader and what kinds of factors are influencing him/her. The results revealed that formally the chairperson of the municipality has no decisive influence on the municipality and that both types of factors (internal and external) interact with each other limiting the political leader’s (chairperson’s of a municipality) freedom of action.